Morphometric study of Labeo nandina, the fresh water endangered cyprinid from Brahmaputra River, Assam and a comparative analysis with four locally available Labeo species - Barman, Anamika; Sharma, D. K. (IJRDO - JOURNAL OF BIOLOGICAL SCIENCE, 2017)
Labeo nandina is an interesting component of the fish diversity of North-East India.It is an endangered cyprinid of the Brahmaputra river system. Due to its polyphyletic origin, this species has nomenclatural and taxonomic ambiguity. Individuals of the same genus living in variety of habitats may be subjected to different environmental conditions. As a result they may adapt to local conditions in those habitats which include changes in morphology from the common phenotype. 10 morphometric parameters like total length (TL), standard length (SL), head length (HL), eye diameter (ED) etc were taken for the morphometric study. Morphometric study was done on Labeo nandina and compared along with four locally available species of Labeo, viz Labeo rohita, Labeo gonius, Labeo calbasu, Labeo bata.. The quantitative data were then analyzed by descriptive statistics obtaining dendrogram using SPSS version 16 software. The dendrogram thus obtained was used for a comparative analysis of Labeo nandina with the four other Labeo species mentioned above. The results showed specific morphological divergence among the species. From the study it was found that Labeo nandina has the highest eye diameter (1.64 cm) and Labeo bata has the lowest eye diameter (0.9cm). The pre orbital length of Labeo nandina is highest (2.7cm) than all the other Labeo species taken.The dendrogram obtained from the analysis of the average measurements of morphometric characters of Labeo nandina with the four locally available species taken, showed three major clusters. Labeo rohita, Labeo calbasu, Labeo gonius formed one cluster, Labeo bata formed another cluster with the above clustered species and finally, Labeo nandina formed the third cluster with the species of the above two clusters. Labeo bata was found to form the closest cluster with Labeo nandina than the species of other cluster formed. This result shows that Labeo nandina has a greater metric similarity with Labeo bata. Next to it L. rohita, L. calbasu and L.gonius shows almost equal similarity with Labeo nandina, in terms of metric characters